Buffer Zone Development for The Sustainability of Gray Langur in The STIK Jantho Aceh Besar Educational Forest - Rosmalia; Aswita; Ruskhanidar Ruskhanidar (Universitas Nusa Bangsa, 2025)
The silver langur (Trachypithecus cristatus) is a primate species protected by law. Its conservation status is listed as Vulnerable in the IUCN Red List data and Appendix II status in CITES. The very sharp decline in the gray langur population is due to declining habitat quality and poaching. The STIK educational forest is a secondary forest, which is disturbed by illegal logging and forest encroachment for community gardens and forest fires. The population data include group sixes and structures were not know well number of groups and individuals in the gray langur is not yet known. The age structure and sex ratio of the gray langur are also not yet known. The composition of the food trees of silver langur in this area is also not yet known. There is no data on those silver langur in the STIK Jantho educational forest. This study aims to obtain data on the gray langur in the STIK Jantho educational forest, including the number of groups, the number of individuals, the age structure, and the sex ratio of the gray langur. Data collection in this study used the line transect method by recording the number of groups, the number of individuals, the age structure, and the sex ratio. Data analysis using Arch GIS 10.1 to determine the distribution of gray langurs by plotting each coordinate obtained, using GPS visualized in the form of a map. Determination of gray langur density using the formula: P = D x A. Found 1 group of Gray langurs (Trachypithecus cristatus), with a total of 10 individuals. The age structure of gray langurs in HP STIK Jantho is included in the developing age category and has a complete composition (Male, adult female, infant, and juveneel).